PENGARUH MODEL PEMBELAJARAN CPS (CREATIVE PROBLEM SOLVING) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V SD SWASTA ISLAM TERPADU BANDAR LAMPUNG - Fitriana Rahmawati (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to determine the effect of the Creative Problem Solving (CPS) learning model on students' mathematical problem solving abilities towards students' mathematical problem solving abilities. This research is an experimental research using a posttest. The population of this study were all students of class V SD Swasta Islam Terpadu Bandar Lampung in the academic year, consisting of 96 students and divided into 3 classes. In this study, the sample used was 64 students divided into two classes (experimental class I and control class). The sample is determined by Random Sampling technique. The results of this study are that the CPS learning model is more effective in influencing problem solving abilities than conventional learning models on students' mathematical problem solving abilities.